2016
DOI: 10.3168/jds.2015-10487
|View full text |Cite
|
Sign up to set email alerts
|

Associated effects of copy number variants on economically important traits in Spanish Holstein dairy cattle

Abstract: Copy number variants (CNV) are structural variants consisting of duplications or deletions of genomic fragments longer than 1 kb that present variability in the population and are heritable. The objective of this study was to identify CNV regions (CNVR) associated with 7 economically important traits (production, functional, and type traits) in Holstein cattle: fat yield, protein yield, somatic cell count, days open, stature, foot angle, and udder depth. Copy number variants were detected by using deep-sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 41 publications
(39 reference statements)
4
41
0
Order By: Relevance
“…After converting 6015 CNVRs to corresponding results based on Btau4.0 using the UCSC liftOver tool with 50% of bases that must remap, 3996 CNVRs of which were successfully converted amounting to about 45.06 Mb. We found that ~80% of the 3996 CNVRs overlapped with those reported by previous investigations [23, 2730] by 1 bp or greater (Fig. 5), and the largest overlap was ~7.92 Mb of the reported by Bickhart et al [23].…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…After converting 6015 CNVRs to corresponding results based on Btau4.0 using the UCSC liftOver tool with 50% of bases that must remap, 3996 CNVRs of which were successfully converted amounting to about 45.06 Mb. We found that ~80% of the 3996 CNVRs overlapped with those reported by previous investigations [23, 2730] by 1 bp or greater (Fig. 5), and the largest overlap was ~7.92 Mb of the reported by Bickhart et al [23].…”
Section: Discussionsupporting
confidence: 74%
“…The number of CNVs (14,821) identified in this study was more than the reports based on NGS data by Bichkhart et al (1265) in Angus, Holstein, Hereford and Nelore cattle [23], Stothard et al (790) in Holstein and Black Angus [28], Zhan et al (520) in Holstein [27], Boussaha et al (957) in Holstein, Montbéliarde and Normande [29] and Ben et al (823) in Holstein [30]. In addition, Jiang et al detected CNVs based on Illumina BovineSNP50 (99) and BovineHD chips (367) data in Chinese Holstein population [24, 25], which were less than what we detected in this study.…”
Section: Discussionmentioning
confidence: 43%
See 2 more Smart Citations
“…Cattle CNVs have been reported using a variety of platforms, including comparative genomic hybridization arrays (Liu et al, 2008, 2010; Fadista et al, 2010), the Illumina BovineHD BeadChip (Hou et al, 2012a; Wu et al, 2015; Aguilar et al, 2016; Prinsen et al, 2016; Xu et al, 2016), the Illumina BovineSNP50 BeadChip (Matukumalli et al, 2009; Bae et al, 2010; Hou et al, 2011, 2012b; Jiang et al, 2012; Bagnato et al, 2015; Ben Sassi et al, 2016), and next-generation sequencing (NGS) (Stothard et al, 2011; Zhan et al, 2011; Bickhart et al, 2012; Choi et al, 2013; Keel et al, 2016; Ben Sassi et al, 2016). In these studies, it is reported that copy number variable regions comprise ~2–7% of the cattle genome.…”
Section: Introductionmentioning
confidence: 99%